Immortal Time Bias-Corrected Effectiveness of Traditional Chinese Medicine in Non-Small Cell Lung Cancer (C-EVID): A Prospective Cohort Study - Zhang, Xing; Guo, Qiujun; Li, Conghuang; Liu, Rui; Xu, Tao; Jin, Zhichao; Xi, Yupeng; Qin, Yinggang; Li, Weidong; Chen, Shuntai; Xu, Ling; Lin, Lizhu; et al. (Frontiers in Oncology, 2022)
Background: Relatively little is known about the effect of traditional Chinese medicine (TCM) on prognosis of non-small cell lung cancer (NSCLC). Methods: In this nationwide, multicenter, prospective, cohort study, eligible patients aged 18-75 years with radical resection, and histologically confirmed stage II-IIIA NSCLC were enrolled. All patients received 4 cycles of standard adjuvant chemotherapy. Patients who received Chinese herbal decoction and (or) oral Chinese patent medicine for a cumulative period of not less than 6 months were defined as TCM group, otherwise they were considered as control group. The primary endpoint was DFS calculated using the Kaplan–Meier method. A time-dependent Cox proportional hazards model was used to correct immortal time bias. The secondary endpoints included DFS in patients of different characteristics, and safety analyses. This study was registered with the Chinese Clinical Trial Registry (ChiCTR1800015776). Results: A total of 507 patients were included (230 patients in the TCM group; 277 patients in the control group). The median follow-up was 32.1 months. 101 (44%) in the TCM group and 186 (67%) in the control group had disease relapse. The median DFS was not reached in the TCM group and was 19.4 months (95% CI, 14.2 to 24.6) in the control group. The adjusted time-dependent HR was 0.61 (95% CI, 0.47 to 0.78), equalling to a 39% reduction in the risk of disease recurrence with TCM. the number needed to treat to prevent one patient from relapsing was 4.29 (95% CI, 3.15 to 6.73) at 5 years. Similar results were observed in most of subgroups. Patients had a significant improvement in white blood cell decrease, nausea, decreased appetite, diarrhea, pain, and fatigue in the TCM group. Conclusion: TCM may improves DFS and has a better tolerability profile in patients with stage II-IIIA NSCLC receiving standard chemotherapy after complete resection compared with those receiving standard chemotherapy alone. Further studies are warranted.